Simulation Study of n-type Double-Gate Nano-MOSFET with Arbitrary Wafer Orientations and Any Channel Materials - Ooi Chek Yee; Wong Pei Voon (Emerging Advances in Integrated Technology, 2025)
In this paper, the technique for quantum mechanically simulating a double-gate (DG) nano-MOSFET with arbitrarily oriented wafer directions and various channel materials is presented. The problem with arbitrarily oriented wafer directions and any channel materials is that the misalignment of principal axes of conduction bands ellipsoids and devices axes causes the matrix and so effective mass equation (EME) become cumbersome to solve. This drawback is overcome by transforming the main axes of the conduction band ellipsoids of the nano-MOSFET to align properly with the device axes, that are transport, confinement and width directions. This transformation technique is discussed theoretically, generally and then simulated specifically for a 10 nm n-type DG nano-MOSFET designed using Silicon (Si) wafer orientation of (100) direction. Two current-voltage (I-V) equations are derived and the calculated on-state current value, are compared with theoretically simulated data 2.500x103 µA/µm. The first and second current model produce of 2.182x103 µA/µm and 2.548x103 µA/µm, respectively. The second model is more accurate since it treats the electron flow as ballistic. This transformation technique enables device engineers to use any device simulator with EME model to study the carriers transport properties of MOSFET with any channel materials (Si, Ge and GaAs) and arbitrary wafer orientations ((100), (110) and (111)). This paper focuses specifically on Si with (100) wafer.